Mengoptimalkan Platform E-Learning Melalui Pembelajaran Adaptif untuk Demografi yang Beragam. - Rodriguez, Marta; Rizky, Agung; Tanjung, Yul Ifda; Sumliyah, Sumliyah (Pandawan Sejahtera Indonesia, 2025)
The rapid growth of e-learning and distance education platforms highlights the need for educational systems that are more inclusive and accessible to diverse demographics and ethnic groups. However, as adoption increases, challenges related to accessibility and personalized learning experiences have become more evident, especially among underrepresented groups. This study explores how adaptive learning technologies can optimize e-learning and distance education platforms to overcome these challenges and improve accessibility for diverse learners. A mixed-methods approach was used, combining surveys, interviews, and case studies with students and educators across various contexts. The study also reviews current adaptive learning technologies and their integration into online environments. The findings show that adaptive technologies significantly enhance learning experiences by personalizing content and delivery according to individual needs, thereby addressing barriers of accessibility and engagement. Moreover, these technologies help bridge educational gaps, ensuring a more equitable learning process for students from different backgrounds. The study concludes that implementing adaptive learning technologies can improve the inclusivity and accessibility of e-learning platforms, making them more effective for diverse demographic and ethnic groups. Further research is recommended to refine these technologies and examine their long-term effects on educational equity.